Protecting forests against illegal logging in Tanzania: Examining the law and practice - Kilonzo, Claudi Christopher (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Master Degree in International Law (LLM-IL) of Mzumbe University